STORYTIME - A Story Narrating App For Children - Dsa, L; Jaiswal, N; Chitodkar, T; Shaikh, Z (International Journal of Computer Sciences and Engineering, 2025)
Audiobooks and Digital eBooks are another way for us to take literature anywhere we want to go, enabling us to tune in to any story anytime we want to. They have become extremely popular recently but they lack emotions in their voice which makes them quite monotonous and tedious. In this paper we present a solution as a mobile application to make reading enjoyable for children. The android application reads the stories aloud with the help of text-to-speech API’s along with the insertion of semantic sounds depending on the rules of natural language processing. The stories are read along with appearance of background images to give it a pleasant visual effect. Our application is implemented using Stanford CoreNLP libraries in Java and Text-to-Speech API’s, which will strengthen the interest of reading in children and make it more fascinating.